Luaran Kehamilan Dengan Sistemik Lupus Eritematosus - Maya Savira (Fakultas Kedokteran Universitas Riau, 2011)
Systemic lupus erythematosus often abbreviated to SLE or lupus, is a systemicautoimmune disease (or autoimmuneconnective tissue disease) that can affect any part ofthe body. As occurs in other autoimmune diseases, the immunesystem attacks the body’scells and tissue, resulting in inflammation and tissue damage. It is a type IIIhypersensitivityreaction caused by antibody-immune complex formation. Women with lupus are at risk for various complications ofpregnancy, and those with antiphospholipid antibodies may have an increased risk of miscarriage. Systemic lupuserythematosus increases the risk of spontaneous abortion, intrauterine fetal death, preeclampsia, intrauterine growthretardation, and preterm birth. The outcome for both mother and child is best when systemic lupus erythematosus hasbeen under good control for at least six months before pregnancy and when the kidney disease is in remission.